2020
DOI: 10.1093/ofid/ofaa414
|View full text |Cite
|
Sign up to set email alerts
|

Use of ICD-10 Codes for Identification of Injection Drug Use–Associated Infective Endocarditis Is Nonspecific and Obscures Critical Findings on Impact of Medications for Opioid Use Disorder

Abstract: Background No International Classification of Diseases 10 th revision (ICD-10) diagnosis code exists for injection drug use-associated infective endocarditis (IDU-IE). Instead, public health researchers regularly use combinations of non-specific ICD-10 codes to identify IDU-IE; however, the accuracy of these codes has not been evaluated. Methods We compared commonly used ICD-10 diagnosis codes for IDU-IE to a prospectively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
0
27
1
Order By: Relevance
“…Moreover, there is a discrepancy in the use of surrogate codes for IE in PWID, as there are no specific ICD-9/10 codes for PWID, resulting in studies reporting varying data for hospitalization of patients for the same year using the same database [ 36 ]. Furthermore, it has been suggested that studies that use ICD-10 for coding of IE in PWID should be viewed with caution, owing to the risk of missing or misclassifying more than half the patients, prompting questions regarding the accuracy of codes [ 37 ]. This demonstrates a need for ICD codes to be standardized and validated with other records before conducting population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is a discrepancy in the use of surrogate codes for IE in PWID, as there are no specific ICD-9/10 codes for PWID, resulting in studies reporting varying data for hospitalization of patients for the same year using the same database [ 36 ]. Furthermore, it has been suggested that studies that use ICD-10 for coding of IE in PWID should be viewed with caution, owing to the risk of missing or misclassifying more than half the patients, prompting questions regarding the accuracy of codes [ 37 ]. This demonstrates a need for ICD codes to be standardized and validated with other records before conducting population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Use of ICD codes without verification of event accuracy is a common practice, and few studies have validated ICD codes for IE. [ 12 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Although diagnosis codes are known to misclassify and severely underestimate ED prevalence of substance use disorders [27][28][29], we characterized the study-site ED population from 2017-2018 using International Classification of Diseases 10 th Edition (ICD-10) codes. Of ED patients, 0.7% had at least one opioid use disorder diagnosis (any F19.X), 0.3% had a diagnosis of intravenous drug use (F19.9), 1% had either a chief complaint or diagnosis code that included the terms "opioid" and "overdose", and 2% had either a chief complaint or diagnosis code that included the term "abscess" [21].…”
Section: Study Design and Settingmentioning
confidence: 99%